Studies on mechanical, fractured surface, wear, and thermal characteristics of TiC reinforced structural grade Al6061 MMCs (Fracture and Structural Integrity, 2025)
Stir casting technique has been used in the current study to process Al6061 reinforced with TiC particles of different concentrations. The processed compounds' composition of TiC and Al6061 has been verified by Energy Dispersive X-Ray Spectroscopy (EDS) tests. TiC has been added to Al6061 in a range of weight concentrations, including 0, 3, 6, 9, and 12%. To determine the composite material's structure, an optical microscope research was used. It is endeavored to investigate the microstructure, mechanical, wear, and thermal performance of TiC-reinforced composites with varying weight fractions in this study. It was observed that, the strength of the developed composites increased by 51.89% in hardness, 18.47% in tensile strength and 40% in wear rate with the addition of TiC. Also, when compared to the alloy material, TiC particle reinforced Al6061 showed superior thermal characteristics.
Keywords: Al6061; TiC; Microstructure; Mechanical properties; Wear behavior; Fractured surface; Thermal conductivity; Thermal expansion coefficient